Analisis Unsur Gharar dalam Akad Wakalah bil Ujrah Pada Produk PRUsyariah: Analysis of Gharar Elements in Wakalah bil Ujrah Contracts in PRUsyariah Products - Hasanah, Wardatul; Sudrajat, Bayu; Soviana, Vriana; Firmansyah, Ahmad Riski; Pangestuti, Yosinta (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This article examines the analysis of the element of gharar (uncertainty or ambiguity) in wakalah bil ujrah contracts within Sharia bancassurance products, with a focus on the PRUsyariah case study. As one of the primary contracts in the Sharia bancassurance scheme, wakalah bil ujrah demands a high level of transparency to avoid transaction practices containing gharar. This study aims to identify potential forms of gharar, assess their categories—whether they constitute gharar fahisy (major uncertainty) or gharar yasir (minor uncertainty)—and evaluate their compliance with muamalah principles and DSN-MUI fatwas. The research employs a normative juridical method through literature review, analysis of PRUsyariah policy documents, and comparison with classical fiqh provisions and DSN fatwas regarding wakalah bil ujrah contracts in the Sharia insurance industry. The results indicate that although the structure of the PRUsyariah contract generally complies with Sharia provisions, there are several potential instances of gharar that must be anticipated, particularly regarding the transparency of benefits, fees, and investment mechanisms. With proper mitigation, potential gharar fahisy can be prevented, ensuring the contract remains valid and product operations proceed according to the principles of fairness and transparency in Sharia economics.